Novel hydrothermal synthesis process of lithium manganese iron phosphate positive electrode material
By synthesizing spherical carbon-coated nano-manganese iron lithium cathode materials using microwave heating and spray pyrolysis technology, the shortcomings of traditional hydrothermal synthesis are overcome, achieving high efficiency, excellent electrochemical performance, and potential for industrial application.
Patent Information
- Application Number
- CN202411181031.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2026-03-06
AI Technical Summary
Traditional hydrothermal synthesis of lithium manganese iron phosphate suffers from problems such as long synthesis cycle, difficulty in controlling particle size, and poor electrochemical performance, which limit its large-scale application.
Microwave heating technology was used to conduct a hydrothermal reaction to synthesize primary nanorod-shaped lithium manganese iron phosphate cathode material particles, which were then formed into spherical materials by spray pyrolysis technology. The surface was coated with a carbon layer, and a composite carbon source and binder were combined to improve the material performance.
Shorten the synthesis cycle, achieve uniform synthesis of nanoscale materials, improve electrochemical performance, reduce production costs, and make it suitable for industrial production.
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, specifically to a novel hydrothermal synthesis process for lithium manganese iron phosphate cathode material. Background Technology
[0002] With the rapid development of electric vehicles (EVs) and energy storage technologies, higher demands are being placed on the energy density, cycle life, and safety of lithium-ion batteries. Lithium manganese iron phosphate (LMFP), as a promising cathode material, has attracted much attention due to its high theoretical capacity and good safety. However, traditional hydrothermal synthesis of LMFP has many shortcomings, such as long synthesis cycle, difficulty in controlling particle size, and poor electrochemical performance, which limit its large-scale application. Summary of the Invention
[0003] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a new hydrothermal synthesis process for lithium manganese iron phosphate cathode materials.
[0004] The technical solution adopted in this invention is as follows: A novel hydrothermal synthesis process for lithium manganese iron phosphate cathode material includes the following steps: Lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate were selected as raw materials and weighed according to the preset Fe and Mn molar ratio. The mixture is stirred and mixed in water to form a precursor solution for lithium manganese iron phosphate cathode material. The precursor solution is then subjected to a hydrothermal reaction using microwave heating technology. By controlling the reaction temperature, time, and microwave power, primary particles of lithium manganese iron phosphate cathode material with a nanorod structure are synthesized. Microwave heating significantly shortens the nucleation time, increases the supersaturation of the solution, and promotes the uniform generation and dispersion of nanocrystals. The primary particles of lithium manganese iron phosphate cathode material are mixed with a composite carbon source and a binder to form a slurry with a certain viscosity. Subsequently, the slurry is treated with spray pyrolysis technology to obtain spherical lithium manganese iron phosphate cathode material with a carbon layer on the surface. The spray pyrolysis lithium manganese iron phosphate cathode material is then dried, sieved, and subjected to electrochemical performance testing.
[0005] According to one embodiment of the present invention, lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate are accurately weighed as raw materials and mixed according to a preset Fe and Mn molar ratio; the weighed raw materials are mixed in an appropriate amount of water under stirring to form a uniform lithium manganese iron phosphate cathode material precursor solution.
[0006] According to one embodiment of the present invention, the precursor liquid is placed in a hydrothermal reactor and connected to a microwave heating device.
[0007] According to one embodiment of the present invention, a microwave heating system is activated to heat the precursor liquid while maintaining stirring to ensure uniform reaction. By controlling the power, reaction temperature, and time of microwave heating, the raw materials in the precursor solution undergo a chemical reaction to generate nanorod-shaped primary particles of lithium manganese iron phosphate cathode material; microwave heating can shorten the nucleation time.
[0008] According to one embodiment of the present invention, primary particles of lithium manganese iron phosphate cathode material are mixed with a composite carbon source, including a soluble carbon source, a two-dimensional carbon material, and a one-dimensional carbon material, and an appropriate amount of binder to form a slurry with a certain viscosity. The prepared slurry is fed into a spray pyrolysis device, where it is atomized into tiny droplets by a spraying device. In a high-temperature pyrolysis chamber, the tiny droplets are rapidly dried and pyrolyzed to form spherical lithium manganese iron phosphate cathode material with a carbon layer on the surface. The use of composite carbon source and binder improves the conductivity, structural stability, and processing performance of the material.
[0009] According to one embodiment of the present invention, the lithium manganese iron phosphate cathode material after spray pyrolysis is dried to remove residual moisture or solvent; the dried material is sieved to obtain a product with the desired particle size distribution; and the final product is subjected to electrochemical performance tests, including charge-discharge cycle, rate performance, and capacity retention, to evaluate whether its electrochemical performance meets the requirements.
[0010] According to one embodiment of the present invention, the prepared lithium manganese iron phosphate cathode material is applied to a lithium-ion battery and assembled into a battery for testing.
[0011] According to one embodiment of the present invention, the overall performance of the battery, including energy density, cycle life, and safety, is evaluated to determine the performance of the cathode material in practical applications.
[0012] In this technical solution, the present invention achieves efficient synthesis and performance optimization of lithium manganese iron phosphate cathode material through a series of meticulous steps; by accurately weighing and mixing raw materials such as lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate, and manganese sulfate monohydrate, and according to a preset Fe and Mn molar ratio, the stoichiometric ratio between reactants is ensured to lay the foundation for subsequent chemical reactions; simultaneously, the raw materials are mixed in water to form a precursor solution, promoting uniform dispersion of the raw materials and facilitating subsequent reactions; utilizing hydrothermal reaction and microwave heating technology, the precursor solution is placed in a hydrothermal reactor and heated by a microwave heating system; the introduction of microwave heating significantly shortens the nucleation time, increases the supersaturation of the solution, and promotes the uniform generation and dispersion of nanocrystals; by precisely controlling the power, reaction temperature, and time of microwave heating, nanorod-shaped primary particles of lithium manganese iron phosphate cathode material are successfully synthesized, providing key raw materials for the preparation of high-performance cathode materials; the primary particles of lithium manganese iron phosphate cathode material are mixed with a composite carbon source and binder to form a slurry with a certain viscosity; the composite carbon source and binder... The addition of manganese iron phosphate (MFP) not only improves the conductivity and structural stability of the material but also enhances its processing performance. Subsequently, the slurry is atomized into tiny droplets using spray pyrolysis technology and rapidly dried and pyrolyzed in a high-temperature pyrolysis chamber to form spherical lithium manganese iron phosphate cathode materials with a carbon layer on the surface. This step further improves the electrochemical and processing performance of the material. The spray-pyrolyzed MFP cathode material is then dried, sieved, and subjected to electrochemical performance testing. Drying removes residual moisture or solvent, and sieving yields products with the desired particle size distribution. Electrochemical performance testing comprehensively evaluates the material's charge-discharge cycle life, rate performance, capacity retention, and other indicators to ensure that the material's electrochemical performance meets requirements. The prepared MFP cathode material is then applied to lithium-ion batteries and assembled for testing. By evaluating the overall battery performance, including energy density, cycle life, and safety, the excellent performance of the cathode material in practical applications is verified. This series of steps not only demonstrates the efficient synthesis method of MFP cathode materials but also reflects their enormous application potential in the field of lithium-ion batteries.
[0013] The present invention has the following beneficial effects: It shortens the synthesis cycle and improves production efficiency; it achieves uniform synthesis and dispersion of nanoscale lithium manganese iron phosphate cathode materials, thereby enhancing the electrochemical performance of the materials; it introduces composite carbon sources and binders to improve the conductivity, structural stability, and processing performance of the materials; it provides a green synthesis route using waste lithium iron phosphate and lithium manganese oxide as raw materials, reducing production costs and realizing resource recycling; it is suitable for industrial production and has high application value and market prospects. Detailed Implementation
[0014] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described content is only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0015] Example 1 This embodiment provides a novel hydrothermal synthesis process for lithium manganese iron phosphate cathode materials, comprising the following steps: Lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate were selected as raw materials and weighed according to the preset Fe and Mn molar ratio. The mixture is stirred and mixed in water to form a precursor solution for lithium manganese iron phosphate cathode material. The precursor solution is then subjected to a hydrothermal reaction using microwave heating technology. By controlling the reaction temperature, time, and microwave power, primary particles of lithium manganese iron phosphate cathode material with a nanorod structure are synthesized. Microwave heating significantly shortens the nucleation time, increases the supersaturation of the solution, and promotes the uniform generation and dispersion of nanocrystals. The primary particles of lithium manganese iron phosphate cathode material are mixed with a composite carbon source and a binder to form a slurry with a certain viscosity. Subsequently, the slurry is treated with spray pyrolysis technology to obtain spherical lithium manganese iron phosphate cathode material with a carbon layer on the surface. The spray pyrolysis lithium manganese iron phosphate cathode material is then dried, sieved, and subjected to electrochemical performance testing.
[0016] According to one embodiment of the present invention, lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate are accurately weighed as raw materials and mixed according to a preset Fe and Mn molar ratio; the weighed raw materials are mixed in an appropriate amount of water under stirring to form a uniform lithium manganese iron phosphate cathode material precursor solution.
[0017] According to one embodiment of the present invention, the precursor liquid is placed in a hydrothermal reactor and connected to a microwave heating device.
[0018] According to one embodiment of the present invention, a microwave heating system is activated to heat the precursor liquid while maintaining stirring to ensure uniform reaction. By controlling the power, reaction temperature, and time of microwave heating, the raw materials in the precursor solution undergo a chemical reaction to generate nanorod-shaped primary particles of lithium manganese iron phosphate cathode material; microwave heating can shorten the nucleation time.
[0019] According to one embodiment of the present invention, primary particles of lithium manganese iron phosphate cathode material are mixed with a composite carbon source, including a soluble carbon source, a two-dimensional carbon material, and a one-dimensional carbon material, and an appropriate amount of binder to form a slurry with a certain viscosity. The prepared slurry is fed into a spray pyrolysis device, where it is atomized into tiny droplets by a spraying device. In a high-temperature pyrolysis chamber, the tiny droplets are rapidly dried and pyrolyzed to form spherical lithium manganese iron phosphate cathode material with a carbon layer on the surface. The use of composite carbon source and binder improves the conductivity, structural stability, and processing performance of the material.
[0020] According to one embodiment of the present invention, the lithium manganese iron phosphate cathode material after spray pyrolysis is dried to remove residual moisture or solvent; the dried material is sieved to obtain a product with the desired particle size distribution; and the final product is subjected to electrochemical performance tests, including charge-discharge cycle, rate performance, and capacity retention, to evaluate whether its electrochemical performance meets the requirements.
[0021] According to one embodiment of the present invention, the prepared lithium manganese iron phosphate cathode material is applied to a lithium-ion battery and assembled into a battery for testing.
[0022] According to one embodiment of the present invention, the overall performance of the battery, including energy density, cycle life, and safety, is evaluated to determine the performance of the cathode material in practical applications.
[0023] The usage process of the above embodiments is as follows: This invention achieves efficient synthesis and performance optimization of lithium manganese iron phosphate cathode materials through a series of meticulous steps. By precisely weighing and mixing raw materials such as lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate, and manganese sulfate monohydrate, and according to a preset Fe to Mn molar ratio, the stoichiometric ratio of reactants is ensured, laying the foundation for subsequent chemical reactions. Simultaneously, the raw materials are mixed in water to form a precursor solution, promoting uniform dispersion and facilitating subsequent reactions. Utilizing hydrothermal reaction and microwave heating technology, the precursor solution is placed in a hydrothermal reactor and heated by a microwave heating system. The introduction of microwave heating significantly shortens the nucleation time, increases the supersaturation of the solution, and promotes the uniform generation and dispersion of nanocrystals. By precisely controlling the microwave heating power, reaction temperature, and time, nanorod-shaped primary particles of lithium manganese iron phosphate cathode materials are successfully synthesized, providing key raw materials for the preparation of high-performance cathode materials. The primary particles of lithium manganese iron phosphate cathode materials are mixed with a composite carbon source and a binder to form a slurry with a certain viscosity. The addition of the composite carbon source and binder does not... This process not only improves the conductivity and structural stability of the material but also enhances its processing performance. Subsequently, the slurry is atomized into tiny droplets using spray pyrolysis technology, and then rapidly dried and pyrolyzed in a high-temperature pyrolysis chamber to form spherical lithium manganese iron phosphate cathode materials with a carbon layer on the surface. This step further improves the electrochemical and processing performance of the material. The spray-pyrolyzed lithium manganese iron phosphate cathode material is then dried, sieved, and subjected to electrochemical performance testing. Drying removes residual moisture or solvent, and sieving yields products with the desired particle size distribution. Electrochemical performance testing comprehensively evaluates the material's charge-discharge cycle life, rate performance, capacity retention, and other indicators to ensure that the material's electrochemical performance meets requirements. The prepared lithium manganese iron phosphate cathode material is then applied to lithium-ion batteries and assembled for testing. By evaluating the overall battery performance, including energy density, cycle life, and safety, the excellent performance of the cathode material in practical applications is verified. This series of steps not only demonstrates the efficient synthesis method of lithium manganese iron phosphate cathode materials but also reflects their enormous application potential in the field of lithium-ion batteries.
Claims
1. A new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material, characterized in that, The method comprises the following steps: Lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate are selected as raw materials and weighed according to a preset Fe and Mn molar ratio; The raw materials are mixed in water under stirring to form a lithium iron manganese phosphate positive electrode material precursor solution; a hydrothermal reaction is performed on the precursor solution by using a microwave heating technology; by controlling the reaction temperature, time and microwave power, lithium iron manganese phosphate positive electrode material primary particles with nanorod structure are synthesized; microwave heating significantly shortens the nucleation time, increases the supersaturation of the solution and promotes the uniform generation and dispersion of nanocrystals; The lithium iron manganese phosphate positive electrode material primary particles are mixed with a composite carbon source and a binder to prepare a slurry with a certain viscosity; then, the slurry is treated by using a spray pyrolysis technology to obtain spherical lithium iron manganese phosphate positive electrode material coated with a carbon layer; the lithium iron manganese phosphate positive electrode material after spray pyrolysis is subjected to drying, screening and other post-processing steps and electrochemical performance testing.
2. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, Lithium hydroxide monohydrate, phosphoric acid, ferrous sulfate heptahydrate and manganese sulfate monohydrate are accurately weighed as raw materials and matched according to a preset Fe and Mn molar ratio; the weighed raw materials are mixed in water under stirring to form a uniform lithium iron manganese phosphate positive electrode material precursor solution.
3. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The precursor solution is placed in a hydrothermal reaction kettle and connected to a microwave heating device.
4. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The microwave heating system is started to heat the precursor solution while maintaining stirring to ensure uniform reaction; By controlling the microwave heating power, reaction temperature and time, the raw materials in the precursor solution undergo a chemical reaction to generate lithium iron manganese phosphate positive electrode material primary particles with nanorod structure; microwave heating can shorten the nucleation time.
5. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The lithium iron manganese phosphate positive electrode material primary particles are mixed with a composite carbon source including a soluble carbon source, a two-dimensional carbon material and a one-dimensional carbon material, and a suitable amount of a binder to form a slurry with a certain viscosity; the prepared slurry is fed into a spray pyrolysis device, and the slurry is atomized into tiny droplets by a spraying device; in a high-temperature pyrolysis chamber, the tiny droplets are rapidly dried and pyrolyzed to form spherical lithium iron manganese phosphate positive electrode material coated with a carbon layer; the use of the composite carbon source and the binder improves the electrical conductivity, structural stability and processability of the material.
6. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The lithium iron manganese phosphate positive electrode material after spray pyrolysis is dried to remove residual moisture or solvent; the dried material is screened to obtain a product with a desired particle size distribution; the final product is subjected to electrochemical performance testing, including charge and discharge cycling, rate performance and capacity retention, to evaluate whether its electrochemical performance meets the requirements.
7. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The prepared lithium iron manganese phosphate positive electrode material is applied to a lithium ion battery, and the battery is assembled and tested.
8. The new process for hydrothermal synthesis of lithium iron manganese phosphate cathode material as claimed in claim 1, wherein, The overall performance of the battery, including energy density, cycle life and safety, is evaluated to determine the performance of the positive electrode material in actual application.